High depression symptomatology and mental pain characterize suicidal psychiatric patients. Issue 1 (31st August 2022) - Pompili, Maurizio; Innamorati, Marco; Erbuto, Denise; Luciano, Mario; Sampogna, Gaia; Abbate-Daga, Giovanni; Barlati, Stefano; Carmassi, Claudia; Castellini, Giovanni; De Fazio, Pasquale; Di Lorenzo, Giorgio; Di Nicola, Marco; et al.
Abstract: Background: Symptoms of depression are transdiagnostic heterogenous features frequently assessed in psychiatric disorders, that impact the response to first-line treatment and are associated with higher suicide risk. This study assessed whether severe mental pain could characterize a specific phenotype of severely depressed high-risk psychiatric patients. We also aimed to analyze differences in treatments administered. Methods: 2, 297 adult patients (1, 404 females and 893 males; mean age = 43.25 years, SD = 15.15) treated in several Italian psychiatric departments. Patients were assessed for psychiatric diagnoses, mental pain, symptoms of depression, hopelessness, and suicide risk. Results: More than 23% of the patients reported high depression symptomatology and high mental pain (HI DEP/HI PAIN). Compared to patients with lower symptoms of depression, HI DEP/HI PAIN is more frequent among females admitted to an inpatient department and is associated with higher hopelessness and suicide risk. In addition, HI DEP/HI PAIN (compared to both patients with lower symptoms of depression and patients with higher symptoms of depression but lower mental pain) were more frequently diagnosed in patients with personality disorders and had different treatments. Conclusions: Patients reporting severe symptoms of depression and high mental pain presented a mixture of particular dangerousness (high trait hopelessness and the presence of suicide ideation with more frequency and less controllability and previous suicide behaviors). The presence of severe mental pain may act synergically in expressing a clinical phenotype that is likewise treated with a more complex therapeutic regime than that administered to those experiencing symptoms of depression without mental pain.